Advances in accounting education teaching and curriculum innovations. Vol. 8 - Schwartz, Bill N.; Catanach, Anthony H. (Emerald, 2007)
Advances in Accounting Education is a refereed, academic research annual whose purpose is to help meet the needs of faculty members interested in ways to improve their classroom instruction. Thoughtful, well-developed articles are published that are readable, relevant and reliable. Articles may be either empirical or non-empirical. They emphasize pedagogy, i.e., explaining how faculty members can improve their teaching methods or how accounting units can improve their curricula/programs. It examines diverse issues such as software use, cultural differences, perceptions of the profession, and more. It emphasizes on pedagogy and how faculty can improve their teaching. It contains peer reviewed articles which include empirical and non-empirical findings.
Keywords: Business & Economics -- Banks & Banking.; Social Science -- General.; Banking.; Accounting -- Study and teaching.; elektronické knihy; electronic books